Perancangan Sistem Pemilihan OSIS Berbasis Web Di SMKS Setih Setio 2 Bungo - Anfal Fernando (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
The election of the student council president is a crucial process in determining student leadership within the school environment. However, the manual system still in use often faces obstacles such as time constraints, potential fraud, and inefficiency. This study aims to design a web-based student council election system as a digital solution to support the democratic process at SMKS Setih Setio 2 Bungo. This research adopts a Research and Development (R&D) method with the Waterfall development model, covering stages such as analysis, design, implementation, testing, and maintenance. The system was developed using PHP and MySQL, and deployed online through a hosting service, allowing access for admins, candidates, and voters without relying on a local network. Key features include data management, automatic vote tallying, and user login security. Testing was carried out using the blackbox method and the distribution of functionality and usability questionnaires to evaluate system performance and user experience. The results indicate that all system features function optimally, with a 100% success rate in functionality testing. Meanwhile, the usability evaluation produced an average score of 93.2%, categorized as “Highly Feasible.” Overall, the system is considered effective, easy to use, and capable of facilitating a more flexible and transparent election process through web-based access. Keywords: Student Council Selection, Web-Based System, Hosting, Design